How sales growth and leverage affect financial distress - Aditya Amanda Pane; Hasbiana Dalimunthe; Rana Fathinah Ananda (Trigin Publisher, 2023)
COVID-19 pandemic had an extraordinary impact on various economic sectors, including the transportation sector. The imposition of social distancing certainly has an impact on the company's financial condition. The purpose of this research was to determine the effect of sales growth and leverage on the financial distress of transportation companies in Indonesia. Sales growth is measured by the change in sales every year and leverage is measured by the Debt to Asset Ratio. The sample used in this research is the financial statements of transportation companies listed on Indonesia Stock Exchange for 2019 - 2023, consist of 118 samples. The analytical method used is multiple regression. From the results of multiple regression analysis, it was found that sales growth did not have a significant effect on financial distress and leverage have a significant effect on financial distress.